Analysis of the Environmental Impacts Generated by an Upper Limb Prosthesis: Design for Children, Adolescents and Adults - Espinoza-Perez, A; Davila-Galvez, S; Santander-Tapia, P; Velastin-Osorio, N; Caceres-Conoman, C; Espinoza-Perez, L (Elsevier B.V., 2025)
In the search to improve life quality for people with a limb deficiency, prostheses play an important role in facilitating reintegration into social and working life due to higher health-related quality of life and employment rates reported among upper limb prosthesis users compared to non-users. In this field, introducing 3D printing for their manufacture has brought new proposals regarding cost reduction, better accessibility, and design customization. However, the environmental impacts of producing these devices are still understudied. In this context, this work aims to analyze the environmental impacts of 3D upper limb prostheses through life cycle assessment methodology, analyzing designs for children, adolescents, and adults. This assessment includes from the design stage to assembly with their respective residues. The ReCiPe Midpoint and Endpoint impact categories were assessed, in addition to calculating equivalencies, for a better understanding. Results show that the production of prostheses for children, adolescents, and adults corresponds to 2.57×10−5 DALY, 5.02×10−5 DALY, and 9.64×10−5 DALY, respectively. Regarding the impacts on biodiversity, the production of prostheses for children, adolescents, and adults corresponds to 1.08×10−7 species.yr, 2.79×10−7 species.yr, and 4.74×10−7 species.yr, respectively. Concerning the impacts of natural resources, the production of prostheses for children, adolescents, and adults corresponds to 0.221 USD2013, 0.436 USD2013, and 0.784 USD2013, respectively. Midpoint and Endpoint categories show that, depending on the category, the relevance of the process impact could vary, changing the strategies to seek a lower environmental impact. Furthermore, the impact of the assembly stage also has different configurations depending on the impact category. Furthermore, results show that energy consumption and Polylactic Acid Biopolymer production from raw materials are the resources with the greatest impact on all the designs. Therefore, renewable energy sources and more efficient 3D printers are required to enhance these prostheses’ benefits. © 2025 Institution of Chemical Engineers
Keywords: Upper limb prosthesis; Life cycle assessment; 3D printing; Sensitivity analysis; Strategies for reducing environmental impact